Uji Coba Persiapan Pembelajaran Tatap Muka Masa Normal Baru PAUD “Tunas Bangsa” Semarang - Aji Supriyanto; Jeffry Alfa Rozaq; Agus Budi Santosa; Hersatoto Listiyono (Jurnal Pengabdian Pada Masyarakat, 2021)
AFTER ONE YEAR OF COVID-19, SEVERAL SCHOOLS HAVE STARTED CONDUCTING TRIALS FOR FACE-TO-FACE LEARNING (PTM) BY IMPLEMENTING HEALTH PROTOCOLS AS A NEW FORM OF NORMAL HABIT. Some parents of "Tunas Bangsa" PAUD want PTM, but others are still worried. Regarding this, PAUD wants to do a PTM trial. The method used in this service is to examine participatory actions by providing assistance, preceded by socialization, followed by counseling and the practice of implementing PTM with standard health protocols. The trial was carried out in 4 PTM times, the results were starting from the PTM to the 3 PAUD children who had started memorizing and getting used to implementing health protocols coherently and correctly. Starting to come, wearing a mask, continued washing your hands with soap through running water, and wiping your hands with a dry tissue. At that time the teacher immediately measured the temperature with a thermogun. The final step is that the students sit in their respective places with a distance of 1.5 meters from each other.